Occupational exposure to mycotoxins: current knowledge and prospects - Viegas, Susana (2018)
Occupational exposure to mycotoxins are supposedly very frequent, but it is rarely reported in the scientific literature. Several recent studies described occupational exposure to the aflatoxin B1 (AFB1) mycotoxin in different occupational settings. Previously, exposure to other mycotoxins was shown in the animal husbandry and food processing sectors, confirming that occupational exposure cannot be negligible. However, no guidelines or standard methodologies are available for helping occupational hygienists to consider mycotoxin exposure in their interventions. This article reviews the literature on this problem and recommends some actions for the better management of this risk factor in occupational settings, especially where environmental conditions are favorable to fungal presence.